Evaluation of Food Access and Food Security Concerns Among Public Health Housing Residents - Cheryl Gaddis; Brad Lian; Nicole Watts; Leontyne Thompson (Georgia Southern University, 2015)
Background: In 2012, food insecurity affected 14.5% of the households in the U.S and 20% in the state of Georgia. Individuals who are food-insecure can experience malnutrition, and social and physical problems. The purpose of this study was to assess food access and security concerns in two counties of the North Central Health District 5-2 (NCHD 5-2) in Georgia and to aid in devising interventions to increase food access and reduce food insecurity. Methods: Data collection involved surveying 399 public housing residents within two NCHD 5-2 counties using the Household Food Security Survey developed by the US Department of Agriculture. The survey contained 24 questions focusing on demographics and household food status and on the severity and prevalence of food access and security. Results: Of the 399 participants, 91.9% reported annual household incomes less than $30,000; 61% (n = 244) reported receiving Supplemental Nutrition Assistance Program (SNAP/food stamps) benefits, 11% (n = 46) received Women, Infants, and Children (WIC) benefits, and 3.3% (n = 13) received Temporary Assistance for Needy Families (TANF). Results for food security status (whether or not families have access to food at all times) showed that 7.3% (n = 29) were classified as high food secure, 22.8% (n = 91) as marginally food secure, 30.6% (n = 122) as low food secure, and 39.3% (n = 157) as very low food secure. Conclusions: Most of the residents with some form of food insecurity received government food assistance, yet still identified as being unable to feed themselves or their families for the month. Recommendations to evaluate this problem include additional research and implementation of public health efforts to address food access and insecurity through policy changes and implementation of programs.